Analysis of the variety of learning difficulties of grade IX students in the online learning system on the material of the human reproductive system at SMP PGRI 9 Pemalang - Ipah Budi Minarti; Eko Retno Mulyaningrum; Amalia Rizki Septi Utami (Institute of Computer Science (IOCS), 2023)
This study aims to determine the variety of learning difficulties of class IX students in the online learning system on the human reproductive system at SMP PGRI 9 Pemalang. This type of research is descriptive research. Data collection was carried out by interviews, distribution of questionnaires or questionnaires, and written tests. The research was conducted with a sample of 120 students class IX at SMP PGRI 9 Pemalang. Based on the research results, it is known that students' learning difficulties include internal and external factors. Health is an internal factor of learning difficulties with the highest percentage of 62.23% and disability is the lowest internal factor of learning difficulties with a percentage of 55.20% while the family environment is an external factor of learning difficulties with the highest percentage of 67.80% and environment society is the external factor with the lowest learning difficulties with a percentage of 52.65%.